Предмет: Алгебра, автор: Vladimir030606

Выполните действия:
1) x^2-4/9-m^2 : x-2/3+m - 2/3-m ; 2) a^2-b^2/7 * 14/a-b * a/(a+b)^2 ; 3) a^2-b^2/(a+b)^2 * 1/a+b - 1-a^2/a-b ; 4) (1/m-1 - m+1/m^2+m+1) : (1+1/m^3-1)

Ответы

Автор ответа: zhenyaM2002
0
 frac{x^2-4}{9-m^2} :  frac{x-2}{3+m} - frac{2}{3-m} = frac{(x-2)(x+2)}{(3-m)(3+m) } *  frac{3+m}{x-2} -  frac{2}{3-m} = \  \ 
= frac{x+2}{3-m} - frac{2}{3-m} = frac{x+2-2}{3-m} = frac{x}{3-m}


 frac{a^2-b^2}{7} *  frac{14}{a-b} * frac{a}{(a+b)^2} =  frac{(a-b)(a+b)*14*a}{7*(a-b)*(a+b)^2} =  frac{2*7*a}{7(a+b)} = frac{2a}{a+b}


 frac{a^2-b^2}{(a+b)^2} *  frac{1}{a+b} -  frac{1-a^2}{a-b} = frac{(a-b)(a+b)*1}{(a+b)^2*(a+b)} -  frac{1-a^2}{a-b} = \  \ 
= frac{a-b}{(a+b)^2} -  frac{1-a^2}{a-b} =  frac{(a-b)^2 -(1-a^2)(a+b)^2}{(a+b)^2(a-b)} =  \  \
дальше тупик, проверь условие, может в этом выражении ошибка...



( frac{1}{m-1} -  frac{m+1}{m^2+m+1} ) : (1+ frac{1}{m^3-1} ) = \  \  =frac{m^2+m+1-(m+1)(m-1)}{m^3-1}  :  frac{m^3-1+1}{m^3-1}= \  \ 
= frac{m^2+m+1-(m^2-1)}{m^3-1} *  frac{m^3-1}{m^3} = frac{m+2}{m^3}



Похожие вопросы
Предмет: Алгебра, автор: Аноним